The Rhytidectomy Scar: Analysis of Patient and Surgeon Perspectives - Kumar, Anisha R.; Lu, Guanning Nina; Lee, Emerson; Kontis, Theda C. (Facial Plastic Surgery, 2022)
An understanding of patient preference is vital for surgeons to create outcomes that align with the goals of patients undergoing cosmetic surgery. This study analyzes the perception of the rhytidectomy scar from the perspective of cosmetic patients and surgeons. Cross-sectional surveys were administered in-person to cosmetic patients and online to facial plastic and reconstructive surgeons in the United States. Participants were presented with standardized lateral view photographs of preauricular scars for 10 patients at least 12 months post rhytidectomy procedure. A variety of rhytidectomy incisions were chosen to include pre- versus post-tragal incisions, blunted hair tuft, hypopigmentation, narrow versus wide scar healing. Participants were asked to rate the outcome of the preauricular rhytidectomy scar using the Likert scale from 1 to 10. Quantitative analysis indicates that while both surgeons and cosmetic patients viewed hypopigmented scars less favorably, surgeons were more concerned with pre-tragal incision and blunted hair tuft. Furthermore, the number of rhytidectomies performed by surgeons resulted in more critical analysis of the scars presented in this study. Qualitative analysis of the frequent use of “natural” in the patient comments suggests the importance of maintaining a sense of “normalcy” as well. In contrast, the surgeon comments are most frequently about the relationship between the scar and surrounding anatomical structures, suggesting a descriptive focus on the technicality of scar placement and subsequent anatomical result. Cosmetic patients are primarily concerned about scar appearance while surgeons are more focused on the technical orientation of the scar. An understanding and comparison of the language and perceptions of surgeons and cosmetic patients regarding rhytidectomy scars are vital in creating aesthetic results and managing patient expectations.
Keywords: rhytidectomy scar; facelift scar; hypopigmented scar; incision placement